2016
DOI: 10.1523/jneurosci.2733-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Brain Network Connectivity Maintains Cognition across the Lifespan Despite Accelerated Decay of Regional Brain Activation

Abstract: The maintenance of wellbeing across the lifespan depends on the preservation of cognitive function. We propose that successful cognitive aging is determined by interactions both within and between large-scale functional brain networks. Such connectivity can be estimated from task-free functional magnetic resonance imaging (fMRI), also known as resting-state fMRI (rs-fMRI). However, common correlational methods are confounded by age-related changes in the neurovascular signaling. To estimate network interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
173
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(199 citation statements)
references
References 77 publications
22
173
1
1
Order By: Relevance
“…Most prominent alterations were increased correlations (e.g., DAN-MN) and decreased anticorrelations (e.g., DMN-SN) between networks in the transition from young to middle adulthood. Our observations strongly support accumulating evidence for enhanced communication between functional networks with aging (Chan et al, 2014; Geerligs et al, 2015; Turner and Spreng, 2015; Gallen et al, 2016; Spreng et al, 2016; Tsvetanov et al, 2016). Increased correlations and decreased anticorrelations between networks both reflect reduced selectivity and specificity in the brain’s intrinsic functional architecture.…”
Section: Discussionsupporting
confidence: 89%
“…Most prominent alterations were increased correlations (e.g., DAN-MN) and decreased anticorrelations (e.g., DMN-SN) between networks in the transition from young to middle adulthood. Our observations strongly support accumulating evidence for enhanced communication between functional networks with aging (Chan et al, 2014; Geerligs et al, 2015; Turner and Spreng, 2015; Gallen et al, 2016; Spreng et al, 2016; Tsvetanov et al, 2016). Increased correlations and decreased anticorrelations between networks both reflect reduced selectivity and specificity in the brain’s intrinsic functional architecture.…”
Section: Discussionsupporting
confidence: 89%
“…However, for this data set, resting‐state fluctuation amplitude (an index of vascular reactivity) did not show any regional age differences (data not presented here). Nonetheless, novel modeling methods such as generative modeling, which allows for the effects of neural connectivity to be separated from the hemodynamic component, have previously been demonstrated to be useful in studies of older adults (Tsvetanov et al., 2016) and should be considered as an alternative to the global removal method we utilized in this study. These factors remain complex methodological issues for the field of brain aging research that require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…High ACE participants displayed lower within-network connectivity in both the discovery and replication datasets. Connectivity within functional networks has been shown to underlie multiple cognitive domains including working memory (Dosenbach et al, 2007; Fair et al, 2007a; Power et al, 2010; Tsvetanov et al, 2016). Decrements in working memory are associated with lower connectivity within default and cingulo-opercular networks (Vaidya and Gordon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the functional connectivity between brain regions as part of larger cognitive systems is critical to maintaining intact executive function (reviewed by Vaidya and Gordon, 2013). A recent large neuroimaging study in healthy adults ages 18–88 demonstrated that the degree of connectivity between and within large-scale brain networks becomes increasingly important to maintaining cognitive performance as we age (Tsvetanov et al, 2016). Additionally, altered neural connectivity has been suggested as a potential marker of menopausal women who may be at risk of late-life cognitive dysfunction (Vega et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation